A sustainable revolution in sisal fiber with enhanced mechanical properties of concrete - Selvam, Vijayan; Muniyandi, Tholkapiyan; Putra Jaya, Ramadhansyah (Bentham Open, 2024)
Introduction: This study provides a comprehensive comparative analysis of conventional concrete (CC) and Sisal Fiber Concrete (SFC) and incorporates sisal fiber into a concrete blend for the M25 grade concrete mix. Methods: In order to evaluate the efficacy of both variations of concrete, mechanical and durability parameters were examined. As compared to CC, the results indicated that SFC had a substantially greater compressive strength. The average compressive strength of SFC at the 28-day was 29.47 N/mm2, which signified a significant incremental percentage growth of 9.58% in comparison to CC. In the same way, SFC exhibited an exceptional flexural strength, as evidenced by its mean value of 7.81 N/mm2, which represented a significant 34.42% improvement in comparison to CC. The Bayesian factor independent sample test yielded a t-test value of 12.495 for compressive strength, accompanied by a p-value below 0.001. These results suggest that the observed difference was statistically significant. Conversely, a t-test value of 19.380 and a p-value below 0.001 were produced by the Bayesian factor independent sample test for flexural strength, both of which further supported the existence of a significant difference. The mean disparity in compressive strength between CC and SFC was 5.1522 N/mm2, with a 95% confidence interval encompassing values between 4.2856 and 6.0188 N/mm2. In a similar manner, the mean discrepancy in flexural strength was 2.0000 N/mm2, accompanied by a 95% confidence interval that varied between 1.7831 and 2.2169 N/mm2. Results: The obtained results provide further evidence that SFC is stronger than CC in both compressive and flexural strength, which is consistent with the results obtained from the frequentist statistical analysis. Conclusion: With its eco-friendly properties, sisal fiber concrete could indeed play a significant role in the future of sustainable construction.